Rancang bangun pabrik plastik dari bahan polietilen food grade - Irene Sri Sukaeni; Arum Yuniari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
The aim of this research is to find out process of production and the relation between cost, sell price and percentage of break even point. Production of capacity planned is 43.200 bottles perday, so that in a year with 288 workday, capacity produced is 12.400.000 bottles. The economical calculation are as follows the total capital is fixed capital + working capital - Rp. 1.489.200.308,00 ; the total production cost is variable cost a year + fixed cost a year = Rp.3.532.949.829,00;. The manufacturing cost = Rp. 285,00 / bottle, the profit calculation before taxing is Rp. 466.230.171,00 and after taxing is Rp. 372.984.136, the pay out period calculation consist of the percentage of profit to return the capital (rate of return) before taxing is 31.30%, after taxing is 25.04% and the pay out period before taxing 2 year 11 months, after taxing 3 year 7 months ; the break even calculation consist of break even point is Rp. 1.988.929.421,00; the percentage of break even point is 49,73% and the capacity of break even point is 6.166.25O bottles